2005
DOI: 10.4269/ajtmh.2005.73.239
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Resistant Malaria in Bangui, Central African Republic: An in Vitro Assessment

Abstract: We used an in vitro isotopic drug sensitivity assay to assess the sensitivity of Plasmodium falciparum isolates collected in Bangui, Central African Republic between March and July 2004. We tested antimalarials that are currently in use in this country (chloroquine, amodiaquine, quinine, and pyrimethamine), antimalarials that will become available in this region in the future (artemisinin and halofantrine), and prophylactic antimalarials (mefloquine, doxycycline, and atovaquone). The proportions of resistant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…However, study inclusion criteria in this range could potentially lead to the exclusion of a considerable proportion of malaria-positive cases in most endemic regions and could introduce a major selection bias. 12 The results obtained by Bacon and others, who used a mean starting parasitemia of 0.75% for their comparison of the SYBR Green I and the HRP2 assay, confirm the good performance of the SYBR Green I assay at higher parasite densities. 8 Particularly under field conditions, where parasite densities tend to be low, a lack in sensitivity can preclude the testing of samples that may otherwise provide valuable information.…”
Section: Discussionmentioning
confidence: 55%
“…However, study inclusion criteria in this range could potentially lead to the exclusion of a considerable proportion of malaria-positive cases in most endemic regions and could introduce a major selection bias. 12 The results obtained by Bacon and others, who used a mean starting parasitemia of 0.75% for their comparison of the SYBR Green I and the HRP2 assay, confirm the good performance of the SYBR Green I assay at higher parasite densities. 8 Particularly under field conditions, where parasite densities tend to be low, a lack in sensitivity can preclude the testing of samples that may otherwise provide valuable information.…”
Section: Discussionmentioning
confidence: 55%
“…Our results suggest that, using an HRP2-based assay, the cutoff for in vitro resistance to CQ might be lowered. AQ often retains efficacy against CQ-resistant parasites, probably due to improved potency over CQ, but in vitro resistance to AQ and MDAQ has been described in Africa (32,55). Our study showed that parasites with IC 50 s above the accepted cutoff for resistance to MDAQ are common in Kampala (58% of tested samples had IC 50 s of Ͼ60 nM).…”
Section: Discussionmentioning
confidence: 70%
“…Of 19,597 isolates tested, just 130 (0.7%) were positive for I164L [3]. The mutation occurs at low level in multiple locations; 3% prevalence in western Kenya [4, 5]; 4% in Blantyre, Malawi [6]; 0.6% in the Central African Republic [7]; 1.1% in Comoros [8]; 1.0% in southern Madagascar [8] and 2% in Angola [9]. So far, it only occurs in significant numbers in Uganda [10, 11] and Rwanda.…”
Section: Introductionmentioning
confidence: 99%